The Impact of Divorce Due to Forced Marriage in Campalagian District, Polewali Mandar Regency - Basri; Hannani; Agus Muchsin; Fikri; Rusdaya Basri (Universitas Muhammadiyah Palu, 2023)
This research analyzes forced marriage's impact in the Campalagian District. Marriage is not just an inner and outer meeting of a man and a woman but is intended to achieve happiness, tranquility, and peace of mind. All humans want a lasting marriage. The method used in this research is empirical normative legal research, the research object of which includes both normative and practical aspects. Normative in this research has positive legal norms and Islamic legal norms. Furthermore, normative legal analysis or Islamic legal norms can be legal norms and legal behavior, and Islamic legal research can be divided into two, namely normative and sociological or empirical. The research results show that: 1) forced marriage in Campalagian District still occurs frequently. From 2019 to 2019, there were 14 cases. 2) The impact of forced marriages in Campalagian District is that they end in divorce and impact family conflict and infidelity.